Socio-Demographic and Clinical Profiles Associated with Sodium Consumption Behaviors in Patients with Non-Dialysis Chronic Kidney Disease: A Study in Myanmar - Hlaing, Kay Thi; Sriyuktasuth, Aurawamon; Phligbua, Warunee (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Sodium consumption behaviors (SCB) play a significant role in the development of kidney failure and associated comorbidities in patients with chronic kidney disease (CKD). Despite the widespread harmful effects of excessive salt consumption, factors influencing SCB in patients with non-dialysis CKD are still little known in Myanmar. No previous study was carried out among Myanmar populations with non-dialysis CKD.Purpose: This study aimed to identify the association between socio-demographic and clinical profiles and SCB in patients with non-dialysis CKD in Myanmar.Methods: Cross-sectional data of 123 patients with non-dialysis CKD, gathered from a tertiary hospital-based study in Myanmar, were analyzed. Non-dialysis CKD patients who had been diagnosed with CKD for more than 3 months were recruited via convenience sampling. Data were collected using demographic and clinical characteristics data form, and Sodium Consumption Behaviors Questionnaire (SCBQ). Descriptive and inferential statistics were employed for data analysis.Results: The mean score of SCB was 31.5 (SD=5.1), indicating quite good behaviors. Participants who had high education (b= -.233, p= .006) and old age (b= -.169, p= .048) were more likely to have good SCB, whereas participants who took antihypertensive medication (b= .304, p= .001) and had comorbidities (b= .232, p= .006) were more likely to have poor SCB.Conclusion: The participants in this study displayed quite favorable SCB. Educational level, age, taking antihypertensive medication, and comorbidity significantly contributed to SCB. Hence, nurses and other healthcare providers should screen patients with these characteristics and provide health education to promote good SCB and prevent the progression of CKD in non-dialysis CKD patients in Myanmar.